Aktivasi Peran Mahasiswa KKN UINSU 125 dalam Peningkatan Pendidikan dan Kesehatan di Desa Sibolangit - Srg, Dini Anggraini; Nurfebia, Karina; Pratama, Dimas; Mughiroh, Hafizul; Jumiati, Ety (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
Sibolangit Village is one of the tourist villages in North Sumatra, this village is located in the Deli Serdang Regency, North Sumatra Province. Limitations in education in terms of accessing the latest learning information create quite a difficult challenge for several schools in Sibolangit Village. The health of the elderly is also of particular concern there. The method for implementing Real Work Lecture (KKN) activities for students at the State Islamic University of North Sumatra to the community consists of work programs JBT (Additional Study Hours), JBM (Evening Study Hours), JBP (Companion Study Hours), Koran Learning, elderly health and stunting counseling . All programs carried out have gone well which can be seen from the enthusiasm of students in participating in all the programs that have been made. in participating in all the programs that have been made and the same is the case with the elderly who regularly take part in gymnastic activities and mothers and children who take part in posyandu and counseling.